2022
DOI: 10.1177/18344909221089368
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the COVID-19 pandemic, risk perception, and perceived social support on public trust in physicians in China: A latent transition analysis

Abstract: A population-based, longitudinal study was conducted among 29 provinces in mainland China to investigate how public trust in physicians (PTP) changed since the outbreak of COVID-19 and how the resulting lockdown and social support contributed to its restoration. The baseline sample ( n = 3,233) was obtained during the period of the most rapid progression of COVID-19 (February 1 to 9, 2020, T1). Follow-up ( n = 1,380) took place during the recovery period (March 17 to 24, T2). Latent profile models and a latent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 61 publications
(108 reference statements)
0
8
0
Order By: Relevance
“…Studies have shown that media communication could impact the development of doctor–patient relationships (Chai, 2017 ; Sartorius et al, 2010). During the epidemic, there was a great deal of media coverage regarding the contributions made by healthcare workers, which also enhanced patients’ trust in doctors (Chen et al, 2022 ). Similarly, the relationship between patients and doctors improved during the outbreak of severe acute respiratory syndrome (SARS) in 2003, but the effect did not last.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that media communication could impact the development of doctor–patient relationships (Chai, 2017 ; Sartorius et al, 2010). During the epidemic, there was a great deal of media coverage regarding the contributions made by healthcare workers, which also enhanced patients’ trust in doctors (Chen et al, 2022 ). Similarly, the relationship between patients and doctors improved during the outbreak of severe acute respiratory syndrome (SARS) in 2003, but the effect did not last.…”
Section: Discussionmentioning
confidence: 99%
“…For studies related to social attitude, Wei et al (2022), from the perspective of functionalist emotion theory (FET), argued that emotion regulation is an adaptive function that makes an important contribution to social functioning and mental health (Aldao et al, 2010;Eisenberg et al, 2000). Zhang et al (2022), from the perspective of social identity (Brown, 2000), indicated that group-based assessment generates group-based emotions such as trust and social satisfaction. Ying et al (2023) from the perspective of the theory of psychological catharsis (Jackson, 1994), demonstrated that people's special preference for anger and aggressive feelings and attitudes is because aggressive expressions help to vent and relieve the tension and anxiety caused by the pandemic.…”
Section: Theories Used In This Special Issuementioning
confidence: 99%
“…In addition to individual mental health, researchers have further explored the impact of COVID-19 at the societal level. For example, focusing on the physician population, Chen et al (2022) explored the trajectory of change in physician–patient trust and found that a shift from moderate to high trust was observed in the blockade area and among those with high social support, and that social support moderated the shift from low to high trust. Wang et al (2023) used big data on microblogs to verify whether the COVID-19 outbreak changed Chinese individualism and collectivism from a cultural perspective.…”
Section: The Covid-19 Pandemic and Social Attitudesmentioning
confidence: 99%
“…While public trust in physicians had declined before the COVID-19 pandemic, the COVID-19 crisis offers an opportunity to restore trust in physicians. A study based on 1350 Chinese adults showed that the COVID-19 epidemic outbreak and lockdown were associated with increased public trust in physicians ( Chen et al, 2022 ). This result, however, may not be generalizable given the cross-sectional nature of the data and the sampling design used.…”
Section: Introductionmentioning
confidence: 99%